2016
DOI: 10.1039/c5cc08642f
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of alkyldiammonium ions within two different cavities of twisted cucurbit[14]uril

Abstract: Binding interactions between twisted cucurbit[14]uril (tQ[14]) and a series of alkyldiammonium ions both in aqueous solution and DMSO media were investigated by NMR spectroscopy and ITC. Experimental data indicate that tQ[14] possesses two kinds of cavities with different space environments, which can encapsulate two or even three guest molecules with suitable shape and size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…The high enthalpy value could result from the stronger hydrophobic contacts between the guest and the inner wall of the host, with a moderate association constant [Ka = (1.06 AE 0.04) 3 10 3 L/mol], 2) The interaction of Q [7] with HMI is both enthalpy-and entropy-driven with an association constant of Ka = (1.90 AE 0.07) 3 10 2 L/mol, 3) For the case of interaction of tQ [14] with guest HMI, the data points (Figure 5c) are indicative of double binding. [20] From the data obtained, we surmise that both binding sequences are entropically favorable processes with j DH j < j TDS j . For both binding sequences, the positive entropy values may be attributed to the expulsion of the high-energy water molecules from the cavity of tQ [14].…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 79%
See 2 more Smart Citations
“…The high enthalpy value could result from the stronger hydrophobic contacts between the guest and the inner wall of the host, with a moderate association constant [Ka = (1.06 AE 0.04) 3 10 3 L/mol], 2) The interaction of Q [7] with HMI is both enthalpy-and entropy-driven with an association constant of Ka = (1.90 AE 0.07) 3 10 2 L/mol, 3) For the case of interaction of tQ [14] with guest HMI, the data points (Figure 5c) are indicative of double binding. [20] From the data obtained, we surmise that both binding sequences are entropically favorable processes with j DH j < j TDS j . For both binding sequences, the positive entropy values may be attributed to the expulsion of the high-energy water molecules from the cavity of tQ [14].…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 79%
“…The resonance of proton Ha displayed an upfield shift of ca. Generally, interaction of a Q[n] with a guest in different solvents, such as D 2 O and [D 6 ]DMSO is likely to result in different NMR spectra in terms of chemical shift, [20] even different interaction modes. The above results revealed that the opportunity of inclusion of a HMI guest is larger than that of exclusion of a HMI guest in the cavity of HHMeQ [6].…”
Section: H Nmr Study Of the Inclusion Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature is rarely observed in conventional supramolecular hosts. [22] In the presentw ork, we have investigated the bindingi nteractions between tQ [14] and the 20 standard AAs in aqueous HCl solution by isothermal titration calorimetry( ITC) and in DCl/D 2 Oa nd [D6]DMSO by 1 HNMR spectroscopy. [23] The results show that tQ [14] displays stronger binding affinity towards AAs with ap ositively charged side chain or ones incorporatinga na romatic ring, and weaker binding affinity towards AAs with an uncharged or negatively chargeds ide chain.…”
mentioning
confidence: 99%
“…In ar ecent study concerned with the binding interactions between tQ [14] and as eries of alkyldiammonium ions in both aqueous solution and [D6]DMSO, we observed as imilars ituation with the binding of HCl salts of butanediamine or hexanediamine;o nly the titration 1 HNMR spectra in [D6]DMSO could be used to distinguish two different host-guest interaction modes. [22] Thus,f or comparison, the titration 1 HNMR spectra of tQ [14] with Lysi n[ D6]DMSO were acquired (Figure 2). The results showedd ifferent binding behavior for tQ [14] in [D6]DMSO as the number of equivalents of Lysw ere increased (Figure 2b to 2f): only one set of amino protons ignals (A ' ,B ' ) and the side-chain proton signals of Lys( b ' , g ' , d ' )w ereo bserved upon the addition of as malla mount of Lys( Figure2b and 2c), suggesting that the tQ [14] host shields both the amino groupsa nd side chain of Lysi n[ D6]DMSO.…”
mentioning
confidence: 99%